Thoughts on how trade, and WTO rules, can contribute to the post-2015 development agenda - Michael Roberts (World Trade Organization (WTO), 2014)
In September 2015, Heads of State and Government will gather in New York to agree the post-2015 development agenda. The role that trade will play in this agenda is neither clear, nor agreed. Yet an open, non-discriminatory, rules-based multilateral trading system underpins sustainable development - a concept that lies at the core of much of the post-2015 debate to date. Indeed, sustainable development is recognized as an objective in the Marrakesh Agreement Establishing the World Trade Organization (WTO). With the aim of stimulating discussion, this paper asks the question of how trade, and WTO rules, can contribute to the post-2015 development agenda? In reply, the author offers some thoughts on 10 contributions that trade, and WTO rules, can make to the post 2015 development agenda. The list is indicative, not exhaustive. The 10 contributions highlight the complex way in which trade and trade policy interact with the evolving debate on the post-2015 development agenda - a debate which encompasses issues ranging from poverty eradication, inclusive growth, climate change mitigation, decent work, food security, access to health services and sustainable development financing, to name but a few of the topics under consideration. The paper organizes the 10 indicative contributions around three headings: trade rules as part of the enabling environment for the achievement of the post-2015 development agenda; the role that trade, and trade policy, can play in meeting specific goals (including possible Sustainable Development Goals); and the contribution that Aid for Trade can make.
Keywords: F1; F13; O19; 330; WTO; Millennium Development Goals; Sustainable Development Goals; Accession; Inclusive Growth; Food Security; Environment; Intellectual Property; Services; Financing for Development; Aid for Trade; Trade in Value Added; Trade Statistics